Effects of cold storage on life‐history traits of Aphidius matricariae. Issue 11 (26th August 2020) - Rezaei, Mehran; Talebi, Ali A.; Fathipour, Yaghoub; Karimzadeh, Javad; Mehrabadi, Mohammad; Reddy, Gadi V.P.
Abstract: Aphidius matricariae Haliday (Hymenoptera: Braconidae) is a polyphagous solitary endoparasitoid, attacking more than 40 species of aphids. This parasitoid is an important commercial product of many companies that produce biological control agents. Storage at low temperature increases the shelf life of many biocontrol agents, allowing companies to provide a steady and sufficient supply of insects for biocontrol programs. In the current study, the effects of cold storage of 1‐day‐old host mummies with A. matricariae for various time periods (5, 10, 15, 20, and 30 days) at 5 °C on the parasitoid's key life‐history traits were investigated. Parameters assessed after storage included adult emergence rate, offspring sex ratio, adult longevity, oviposition period, fecundity, and life‐table parameters (R0, r, λ, T, and DT). Our results showed that the mummies of A. matricariae could be stored at 5 °C for 5 days without loss of quality and for 10–15 days with minimal reduction in quality (e.g., some reduction in adult longevity and R0 ). If parasitoids were stored for >15 days, quality was more strongly affected. In conclusion, A. matricariae pupae could be stored at 5 °C for up to 15 days without significant negative post‐storage effects on fitness of the parasitoid. These results could be used to improve the planning of mass rearing and mass release of A. matricariae in augmentative biological control programs. Abstract : Aphidius matricariae (Hymenoptera: Braconidae) is a polyphagous solitary endoparasitoid, commercially sold as an aphid control agent. Storage at low temperature increases the shelf life of many biocontrol agents. We studied the effect of storage at 5 °C for 5–30 days on various quality parameters. It turns out that 1‐day‐old mummies of A. matricariae can be stored for up to 15 days with minimal reduction in parasitoid fitness. These results help improve the mass rearing and mass release of A. matricariae .